Lactoferrin-Containing Immunocomplexes Drive the Conversion of Human Macrophages from M2- into M1-like Phenotype - Gao, Chen-Hui; Dong, Hong-Liang; Tai, Li; Gao, Xiao-Ming (Frontiers in Immunology, 2018)
Macrophages are multifunctional cells that perform diverse roles in health and disease, and considered the main source of inflammatory cytokines in affected joints of patients with rheumatoid arthritis (RA). M2 macrophages are well known as anti-inflammation and wound-healing cells; however recent evidence suggests that they can also promote inflammation in RA, although the underlying mechanism remains to be clarified. Based upon our recent finding that lactoferrin (LTF)-containing IgG immunocomplex (LTF-IC), found elevated in RA sera, potent activators of human monocytes/macrophages, we herein demonstrate that LTF-IC was able to elicit immediate pro-inflammatory cytokine production by M2-polarized human macrophages through co-ligation with CD14/TLR4 and FcgRIIa (CD32a). The LTF-IC-treated M2 cells adopted surface maker expression profile similar to that of M1 phenotype and became functionally hyperactive to subsequent stimuli such as LPS, zymosan and IL-1b, which could provide a positive feedback signal to promote excessive inflammation in RA. They also acquired the ability to facilitate activation of Th17 cells that are known to play critical roles in RA pathology. We propose that IgG ICs containing TLR agonizing autoantigens are able to directly switch human macrophages from M2 into M1-like phenotype, thereby promoting excessive inflammation in autoimmune diseases such as RA.